The Effect of Organizational Commitment, Employee Engagement and Training on Employee Performance of Energy Supply Chain Company - Syech Idrus; Ismuhadi; Musran Munizu; Pipin Sri Sudewi; Abdurohim (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2023)
This study's goal is to investigate the effects of employee training and engagement on workers' performance, with organizational commitment acting as a bridging variable. Data for this study was gathered quantitatively from employees in one of supply chain company in Indonesia. Employing a probability sampling approach as a sample technique. Path analysis was employed as a data analysis approach in this study with the use of the analytic program SPSS. The study's findings include a significant positive relationship between employee engagement and organizational commitment, a significant positive relationship between employee engagement and training, a significant positive relationship between employee engagement and training, and a significant positive relationship between employee engagement and employee performance. Training has a very favorable impact on staff performance. Organizational commitment has an impact on employees' performance. Organizational commitment, training, and employee engagement all have an impact on employee performance. This study is anticipated to be utilized as a resource for thought, the sharing of concepts, and the introduction of alternative solutions to issues in businesses pertaining to employee engagement and training that are beneficial in enhancing It is anticipated that this will enhance worker performance and eventually aid in the accomplishment of corporate objectives.